Oligodendroglioma showing pleomorphic xanthoastrocytoma‐like perivascular microlesion: With IDH1, TERT promoter mutation and 1p/19q codeletion detected in both components. Issue 1 (19th December 2019) - Murakami, Chiaki; Ikota, Hayato; Nobusawa, Sumihito; Nakata, Satoshi; Yamazaki, Tatsuya; Hashiba, Yasuhiro; Hirato, Junko; Yokoo, Hideaki
Abstract : We report a histological and genetic study of concurrent oligodendroglioma and a microscopic pleomorphic xanthoastrocytoma (PXA)‐like lesion in a 48‐year‐old male. He presented with generalized seizure, and magnetic resonance imaging revealed a nonenhanced left frontal lobe mass suggesting low‐grade glioma. The patient underwent craniotomy and tumor resection. Histopathological examination of the surgical specimen showed an oligodendroglioma with a PXA‐like element; the latter measured 0.9 mm and occupied a Virchow‐Robin space of the superficial cortex. The whole tumor had no elevated mitotic activity, microvascular proliferation or necrosis. Each component was immunohistochemically isocitrate dehydrogenase (IDH1)‐R132H positive, p53 negative and ATRX positive. Genetic analyses clarified identical IDH1 G395A mutation, promoter C228T mutation and 1p/19q codeletion in both elements. Careful integration of histology and telomerase reverse transcriptase ( TERT ) molecular parameters revealed that this case was an oligodendroglioma showing PXA‐like features, rather than a collision tumor. This case provides further insights into the gliomagenesis.